2004
DOI: 10.1126/science.1098096
|View full text |Cite
|
Sign up to set email alerts
|

Msx1 Cooperates with Histone H1b for Inhibition of Transcription and Myogenesis

Abstract: During embryogenesis, differentiation of skeletal muscle is regulated by transcription factors that include members of the Msx homeoprotein family. By investigating Msx1 function in repression of myogenic gene expression, we identified a physical interaction between Msx1 and H1b, a specific isoform of mouse histone H1. We found that Msx1 and H1b bind to a key regulatory element of MyoD, a central regulator of skeletal muscle differentiation, where they induce repressed chromatin. Moreover, Msx1 and H1b coopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
224
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(234 citation statements)
references
References 24 publications
7
224
0
3
Order By: Relevance
“…Msx-1 is implicated in inhibiting the differentiation of several mesenchymal lineages, including skeletal muscle, during embryogenesis (Bendall et al, 1999;Bendall and Abate-Shen, 2000). When looking for interacting partners for Msx-1 in C2C12 myoblasts Lee et al, found that it preferentially binds to the linker histone H1b (Lee et al, 2004). Linker histones are so called because of their role in keeping the nucleosomes juxtaposed, to form a highly compacted chromatin structure.…”
Section: Stage 1-acquisition Of the Myogenic Lineagementioning
confidence: 99%
See 3 more Smart Citations
“…Msx-1 is implicated in inhibiting the differentiation of several mesenchymal lineages, including skeletal muscle, during embryogenesis (Bendall et al, 1999;Bendall and Abate-Shen, 2000). When looking for interacting partners for Msx-1 in C2C12 myoblasts Lee et al, found that it preferentially binds to the linker histone H1b (Lee et al, 2004). Linker histones are so called because of their role in keeping the nucleosomes juxtaposed, to form a highly compacted chromatin structure.…”
Section: Stage 1-acquisition Of the Myogenic Lineagementioning
confidence: 99%
“…Other events, such as Msx1-dependent positioning of H1b histone (Lee et al, 2004) and Rho-mediated signalling (Carnac et al, 1998) must provide additional elements contributing to induce MyoD expression in muscle cells, although the relationship between these events remains unknown.…”
Section: Behind the Chromatin: Dna Methylation Changes During Myogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to functioning as an important regulator of limb and muscle development, 59,71 Msx1 has also been suggested as being able to promote dedifferentiation of muscle cells and to maintain the multipotency of stem cells. 48,72,73 In a previous study, we observed that Msx1 overexpression in muscle cells resulted in a greatly improved ratio of cells positive for Sca-1 to cells positive for CD34 (unpublished data). We also reported that traumatic injury is able to stimulate skeletal muscle cell dedifferentiation in vivo.…”
Section: Discussionmentioning
confidence: 80%